GEOPHYSICAL RESEARCHES IN THE SEARCH FOR POINTS OF BURIAL RADIOACTIVELY CONTAMINATED MATERIALS - Reva, M.; Onyshchuk, V.; Onyshchuk, D.; Petruniak, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The features of method and results of geophysical prospecting are examined at the searches of disposal place points of radioactivity materials. The example of application of radiometry on the one of areas of Chornobyl APS' alienation zone is resulted.